Improved Long-term Outcomes of Patients With Inflammatory Bowel Disease Receiving Proactive Compared With Reactive Monitoring of Serum Concentrations of Infliximab - Papamichael, Konstantinos; Chachu, Karen A; Vajravelu, Ravy K; Vaughn, Byron P; Ni, Josephine; Osterman, Mark T; Cheifetz, Adam S (Clinical gastroenterology and hepatology, 2017)
Monitoring serum concentrations of tumor necrosis factor antagonists in patients receiving these drugs as treatment for inflammatory bowel disease (IBD), also called therapeutic drug monitoring, is performed either after patient loss of response (reactive drug monitoring) or in patients in clinical remission in which the drug is titrated to a target concentration (proactive drug monitoring). We compared long-term outcomes of patients with IBD undergoing proactive vs reactive monitoring of serum concentrations of infliximab. We performed a multicenter, retrospective study of 264 consecutive patients with IBD (167 with Crohn's disease) receiving infliximab maintenance therapy. The subjects received proactive (n = 130) or reactive (n = 134) drug monitoring, based on measurements of first infliximab concentration and antibodies to infliximab, from September 2006 to January 2015; they were followed through December 2015 (median time of 2.4 years). We analyzed time to treatment failure, first IBD-related surgery or hospitalization, serious infusion reaction, and detection of antibodies to infliximab. Treatment failure was defined as drug discontinuation for loss of response or serious adverse event, or need for surgery. Multiple Cox regression analysis independently associated proactive drug monitoring, compared with reactive monitoring, with reduced risk for treatment failure (hazard ratio [HR], 0.16; 95% confidence interval [CI], 0.09-0.27; P < .001), IBD-related surgery (HR, 0.30; 95% CI, 0.11-0.80; P = .017), IBD-related hospitalization (HR, 0.16; 95% CI, 0.07-0.33; P < .001), antibodies to infliximab (HR, 0.25; 95% CI, 0.07-0.84; P = .025), and serious infusion reaction (HR, 0.17; 95% CI, 0.04-0.78; P = .023). In a retrospective analysis of patients with IBD receiving proactive vs reactive monitoring of serum concentration of infliximab, proactive monitoring was associated with better clinical outcomes, including greater drug durability, less need for IBD-related surgery or hospitalization, and lower risk of antibodies to infliximab or serious infusion reactions.